Effect of heating on the stability of amyloid A (AA) fibrils and the intra- and cross-species transmission of AA amyloidosis. (2nd October 2015) - Ogawa, Saki; Murakami, Tomoaki; Inoshima, Yasuo; Ishiguro, Naotaka
Abstract: Amyloid A (AA) amyloidosis is a protein misfolding disease characterized by extracellular deposition of AA fibrils. AA fibrils are found in several tissues from food animals with AA amyloidosis. For hygienic purposes, heating is widely used to inactivate microbes in food, but it is uncertain whether heating is sufficient to inactivate AA fibrils and prevent intra- or cross-species transmission. We examined the effect of heating (at 60 °C or 100 °C) and autoclaving (at 121 °C or 135 °C) on murine and bovine AA fibrils using Western blot analysis, transmission electron microscopy (TEM), and mouse model transmission experiments. TEM revealed that a mixture of AA fibrils and amorphous aggregates appeared after heating at 100 °C, whereas autoclaving at 135 °C produced large amorphous aggregates. AA fibrils retained antigen specificity in Western blot analysis when heated at 100 °C or autoclaved at 121 °C, but not when autoclaved at 135 °C. Transmissible pathogenicity of murine and bovine AA fibrils subjected to heating (at 60 °C or 100 °C) was significantly stimulated and resulted in amyloid deposition in mice. Autoclaving of murine AA fibrils at 121 °C or 135 °C significantly decreased amyloid deposition. Moreover, amyloid deposition in mice injected with murine AA fibrils was more severe than that in mice injected with bovine AA fibrils. Bovine AA fibrils autoclaved at 121 °C or 135 °C did not induce amyloid deposition in mice. These results suggest that AA fibrils are relatively heat stable and that similar to prions, autoclaving at 135 °C is required to destroy the pathogenicity of AA fibrils. These findings may contribute to the prevention of AA fibril transmission through food materials to different animals and especially to humans.